DEVELOPMENT OF SMALL AND MIKRO INDUSTRIES (UKM) IN JAMBI - Arna Suryani (Universitas Batanghari Jambi, 2016)
The purpose of this research is to: (1) indentify internal and external factors small and mikro industries (UKM) in Jambi (2) what are the threat, opportunities, weaknesses and strengs UKM in Jambi, (3) formulation of development strategies what should be done UKM in Jambi. The object of this research issmall and mikro industries (UKM) in Jambi from April to August 2016 period, with sampel selection by purposive sampling. This study was conducted to determine how the strategy of development of small and mikro industries (UKM) in the city of Jambi in order to grow more rapidly, the poblems faced can be reduced and have a competitive advantage. This study conducted by descriptive statistical approach. The process of data analysis conducted in two stages. The first phase of data collection or input stage using a matrix factor evaluation and external factor evaluation. The second stage is matching using external and internal matrixs and SWOT matrixs. The results showed that small and micro industries in the city of Jambi has the potencial to grow. Development strategy small and mikro industries (UKM) in the city of Jambi is a ST strategy which strategy to use strengs to counter the threats. This strategy should small and mikro industries (UKM) in the city of Jambi diversifying precision products using the technology, improve product qulity, and foster intersive cooperation with suppliers to obtain adequate suppliers of raw materials. Key Words: Small and mikro industries (UKM), internal inveronment, exsternal inveronment, SWOT analysis (Streng, Weakness, Opportunities and Threat)